3D Printing for Chemical Process Laboratories II: Measuring Liquid‐Solid Mass Transfer Coefficients. Issue 4 (1st March 2018) - Gelhausen, Marius Gerrit; Lenz, Daniel; Krull, Fabian; Korkmaz, Vedat; Agar, David William
Abstract: The sulfonation of solid acrylonitrile‐butadiene‐styrene, a feedstock that is often used in the 3D printing process of fused filament fabrication, and its application in characterizing liquid‐solid mass transfer is reported. The ion‐exchange capacity was assessed experimentally, and intraparticle diffusion coupled with extraparticle liquid‐solid mass transfer was simulated. Tubular reactors and spherical particles were fabricated by 3D printing, modified by sulfonation, and used to determine mass transfer coefficients for laminar flow in a tubular reactor and a fixed bed of spherical particles. The results show good agreement with published correlations and demonstrate the applicability of this cost‐effective, accurate, and reliable method. Abstract : Sulfonated polymers have applications in water softening, acid catalysis, and measuring mass transfer rates. Herein, mass transfer coefficients for laminar flow were determined in a 3D‐printed tubular reactor and a fixed bed of spherical particles, both modified by sulfonation, and the obtained values showed good agreement with correlations in the literature.